Analyses of Bioactive Compounds of Pegagan (Centella Asiatica (L.) Urb) from Samosir “ Indonesia Accession - Noverita Sprinse Vinolina; Riswanti Sigalingging (Talenta Publisher, 2022)
Centella Asiatica or Pegagan is classified as one of the wild plants that has not been domesticated. The excessive usage of this plant in traditional and modern medicinal applications threatens its population and sustainability. Thus, to preserve the plant and supply the high request of this plant in agromedicinal industry, studies concerned with the growth and bioactive compounds of Pegagan cultivated under commercial field conditions are urgently needed. This study purposed to examine the bioactive components of Pegagan (especially in leaves and roots) under field conditions, including asiaticoside, madeccasoside, and Asiatic acid. The Pegagan was harvested weeks after planting (WAP). The wet and dry weights of the leaves and roots were weighted and subsequently measured for their centelloside compounds by Thin-Layer Chromatography (TLC) procedure. The results revealed that the resulting asiaticoside content in the roots (1.25%) was higher than in the leaves (0.88%). The same results were achieved for the madecassoside content where the madecasosside content in the roots was 2.23%, while the content in the leaves was 2.11%. However, contrarily, the Asiatic acid compound in the leaves was 1.10% higher than the content in the roots (0.60%). It might be attributed to a longer period of field cultivation of Pegagan that delivered adequate time for the plant to alter Asiatic acid to asiaticoside and madecasosside at a later developmental growth. Moreover, these discoveries are advantageous in defining the most proper harvest time for commercial field cultivation of Pegagan to yield the highest amount of certain centelloside compounds.